Why Do We Disagree about our Obligations to the Poor? - Seipel, Peter (Ethical theory and moral practice, 2019)
People disagree about whether individuals in rich countries like the United States have an obligation to aid the world's poorest people. A tempting thought is that this disagreement comes down to a non-moral matter. I argue that we should be suspicious of this view. Drawing on psychological evidence, I show that we should be more pessimistic about our ability to attribute the disagreement to a difference in factual beliefs.